(untitled) (Journal of the Bangladesh Agricultural University, 2011)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during Boro season of 2008 with a view to examining the effect of soil and foliar application of urea on the yield and nutrient uptake of BRRIdhan 29 and to evaluate whether urea foliar application (FA) could replace its soil application (SA) in the rice cultivation. The experiment was laid out in a randomized complete block design (RCBD) with eight treatments, each treatment replicated thrice. The treatments were: T1 (control), T2 (282 kg urea ha-1 SA), T3 (1% urea solution FA), T4 (2% urea solution FA), T5 (3% urea solution FA), T6 (94 kg urea ha-1 SA + 1% urea solution FA), T7 (94 kg urea ha-1 SA + 2% urea solution FA) and T8 (94 kg urea ha-1 SA + 3% urea solution FA). The results showed that soil and foliar application of nitrogen significantly influenced the growth and yield of crop. The treatment T2 (282 kg urea ha-1) produced the highest grain yield (5.34 t ha-1). The T6 (94 kg urea ha-1 + 1% urea solution FA) produced the highest straw yield (6.58 t ha-1) of the crop. The lowest grain yield (3.20 t ha-1) and the lowest straw yield (4.19 t ha-1) were recorded with T1 (control). Economic analysis showed that treatment T2 gave the highest marginal benefit cost ratio (7.65) while the lowest value (2.71) was observed with T5 treatment. The overall results demonstrated that soil application of 282 kg urea ha-1 was the best treatment for obtaining higher grain yield, higher nitrogen content of rice and higher marginal benefit cost ratio, and soil application is better than foliar application of urea. Keywords: Urea, Nitrogen; Foliar application; Soil application DOI: 10.3329/jbau.v8i2.7925 J. Bangladesh Agril. Univ. 8(2): 199-202, 2010